The Influence of Er: YAG Laser, Alumi-num oxide and diamond bur on surface treatment of Aged Composite Resin to Repair Restoration - Nadia H. Hasan (University of Mosul, College of Dentistry, 2012)
Aim of this study is to investigate the effect of Er: YAG Laser, the sand blasted with aluminum oxide and wearing with diamond bur as a surface treatment to the bond strength of repaired composite resin after aged. Materials and Methods: Sixty Teflon mold (4mm×2mm), of Tetric® Ceram prepared. The specimens were randomly separated into six groups and undergo the following surface treatments: G1 no treatment (control), G2-G4 treated with a different amount of laser energy (40, 60, 80 mJ Er: YAG laser respectively) under a 2Hz frequency, G5 wearing with diamond bur, and G6 sandblasted with 50μm aluminum oxide. All 6 groups divided into two subgroups,1st control,2ed etched with 37% phosphoric acid. Bonding material was applied and the second split of Teflon mold (4mm×1mm) placed onto the prepared specimen, filled with Tetric N-Ceram. The shear test was done using the Uni-versal testing machine. Results: Significant differences of all variables, laser 60,40mj surface treatment displayed superior shear strength (45.24, 45.03 MPa respectively), aluminum oxide showed low shear value (32.48 MPa). Phosphoric acid showed the highest shear value (40.47 MPa) in compare to the control one (31.62 MPa). Conclusions: Using of Er:YAG laser improve the shear value of repaired composite in comparing with a diamond bur and aluminum oxide. Conditioning aged composite surface with a phosphoric acid enhancing its adhesive result.